Development Of QRS Detection Algoritm For FPGA Implementation - Ong, Seng Hooi (2003)
The main objective of this research is to design a chip using the best -optimized QRS complex detection algorithm for FPGA. Hence, VHDL behavioral and structural modeling techniques will be essential part of the design.